Integrasi Nilai-Nilai Syariah dalam Sistem Hukum untuk Penguatan Stabilitas dan Pertumbuhan Ekonomi Islam - Ahmad Akbar Rudin; Eko Filtra (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The purpose of this study is to analyze the contribution of integrating Sharia values into the legal system to strengthening the stability and growth of the Islamic economy, with a focus on the national context and global relevance. The background of the problem stems from the significant growth of the Islamic financial sector in Indonesia, accompanied by challenges in harmonizing regulations between positive law and Sharia law. The urgency of this study lies in the need for consistent, adaptive, and sustainable legal policy formulation to ensure the continuity of growth while maintaining macroeconomic stability. This research uses a qualitative-descriptive approach with legal-economic analysis, processing secondary data from the OJK, Bank Indonesia, BPS, Ministry of Finance, and international reports, supplemented by a review of legal documents such as laws and fatwas from the DSN-MUI. The novelty of this research lies in the integration of legal analysis and current Islamic financial performance indicators into a single evaluation framework, which captures the direct relationship between regulation, governance, and economic performance.The results of the study show that the integration of sharia values, as reflected in asset growth, increased market share, sound financing quality, and high levels of capital and liquidity, can create a stable, inclusive, and efficient financial ecosystem.